Analisis Pengaruh Pendidikan, Kesehatan dan Pengeluaran Per-Kapita Terhadap Kemiskinan di Papua Tahun 2019-2023 - Rabbani, Ahmad Fakhri; Satria Arya Pamungkas; Aidil Fitriansyah; Fajar Muhammad Hasby; Fikri Abdussalam; Calendula Aprido Yurni; Suraya Murcitaningrum (Indonesian Journal Publisher, 2025)
This study investigates the impact of education, health, and per capita expenditure on poverty levels in Papua Province from 2019 to 2023. Employing a quantitative approach, the analysis utilizes panel data regression with the Fixed Effect Model (FEM) as the selected method. The research relies on secondary data sourced from the Central Statistics Agency (BPS) of Papua, and statistical processing is conducted using Eviews 10. The independent variables include education, health, and per capita expenditure, while poverty serves as the dependent variable. The findings reveal that both education and per capita expenditure have a statistically significant negative effect on poverty, indicating that higher educational attainment and greater purchasing power contribute to reducing poverty rates in the region. Conversely, the health variable exhibits a significant positive relationship with poverty, likely reflecting the high cost and limited accessibility of healthcare services in Papua. The regression model demonstrates an Adjusted R² value of 68.64%, suggesting that the three variables collectively account for 68.64% of the variation in poverty levels, with the remaining variance attributed to other unobserved factors. These results underscore the critical need for policies that enhance educational access and improve household purchasing power, as well as reforms aimed at making healthcare services more equitable and affordable. Such measures are essential to effectively address poverty in Papua Province